Junctional E-cadherin/p120-catenin Is Correlated with the Absence of Supporting Cells to Hair Cells Conversion in Postnatal Mice Cochleae - Luo, Wen-wei; Wang, Xin-wei; Ma, Rui; Chi, Fang-lu; Chen, Ping; Cong, Ning; Gu, Yu-yan; Ren, Dong-dong; Yang, Juan-mei (Frontiers in Molecular Neuroscience, 2018)
Notch inhibition is known to generate supernumerary hair cells (HCs) at the expense of supporting cells (SCs) in the mammalian inner ear. However, inhibition of Notch activity becomes progressively less effective at inducing SC-to-HC conversion in the postnatal cochlea and balance organs as the animal ages. It has been suggested that the SC-to-HC conversion capacity is inversely correlated with E-cadherin accumulation in postnatal mammalian utricles. However, whether E-cadherin localization is linked to the SC-to-HC conversion capacity in the mammalian inner ear is poorly understood. In the present study, we treated cochleae from postnatal day 0 (P0) with the Notch signaling inhibitor DAPT and observed apparent SC-to-HC conversion along with E-cadherin/p120ctn disruption in the sensory region. In addition, the SC-to-HC conversion capacity and E-cadherin/p120ctn disorganization were robust in the apex but decreased toward the base. We further demonstrated that the ability to regenerate HCs and the disruption of E-cadherin/p120ctn concomitantly decreased with age and ceased at P7, even after extended DAPT treatments. This timing is consistent with E-cadherin/p120ctn accumulation in the postnatal cochleae. These results suggest that the decreasing capacity of SCs to transdifferentiate into HCs correlates with E-cadherin/p120ctn localization in the postnatal cochleae, which might account for the absence of SC-to-HC conversion in the mammalian cochlea.